ROLE OF ORGANIZATIONAL CULTURE MODERATE EFFECT ORGANIZATIONAL COMMITMENT AND MOTIVATION OF WORK PERFORMANCE OF TEACHERS (Studies in Senior High School Teachers in District Pati City ) - Suwargono, 12.52.02.0189; Srimindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether organizational culture moderates the influence of organizational commitment and work motivation on the performance of a high school teacher in the District City State Pati. The population is used as the object is State high school teachers in the district of the City Pati which amounts to 164 people. Sampling Convenience sampling method using Slovin formula so that it can be seen that the number of samples in this study were 116 respondents. Mechanical testing of the data used in this study include testing the validity of the factor analysis, test reliability with Cronbach alpha formula, multiple regression analysis, and tests of significance, coefficient of determination to prove the truth of the hypothesis of research and testing moderation. The results showed that; organizational commitment significantly influence the performance of teachers, motivation significant effect on the performance of the teacher, organizational culture significantly influence the performance of teachers, organizational culture moderates the influence of organizational commitment on teacher performance, organizational culture also proved capable moderate the influence of motivation to work on teacher performance. Keywords: organizational commitment, job motivation, organizational culture, teacher performance.